2020
DOI: 10.1111/ppa.13266
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenetic roles of beet necrotic yellow vein virus RNA5 in the exacerbation of symptoms and yield reduction, development of scab‐like symptoms, and Rz1‐resistance breaking in sugar beet

Abstract: Beet necrotic yellow vein virus (BNYVV) generally has a four-segmented positivesense RNA genome (RNAs 1-4), but some European and most Asian strains have an additional segment, RNA5. This study examined the effect of RNA5 and RNA3 on different sugar beet cultivars using a Polymyxa-mediated inoculation system under field and laboratory conditions. In field tests, the degree of sugar yield served as an index for assessing the virulence of BNYVV strains. Japanese A-II type isolates without RNA5 caused mostly 15%-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 38 publications
(126 reference statements)
1
16
0
Order By: Relevance
“…It seems unlikely that original D, O, and T strains of BNYVV were directly involved in RB (such as seen in Europe and the United States) because they were already present before cultivating resistant cultivars. However, differences in virulence to Rz1-resistant sugar beet cultivars were previously shown among three strains (Chiba et al, 2011;Tamada et al, 2021). For example, in field tests, a T-type iso- variants were most commonly present, followed by P-type variants (p25, SYHG tetrad); mixed infections of these types were also found.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…It seems unlikely that original D, O, and T strains of BNYVV were directly involved in RB (such as seen in Europe and the United States) because they were already present before cultivating resistant cultivars. However, differences in virulence to Rz1-resistant sugar beet cultivars were previously shown among three strains (Chiba et al, 2011;Tamada et al, 2021). For example, in field tests, a T-type iso- variants were most commonly present, followed by P-type variants (p25, SYHG tetrad); mixed infections of these types were also found.…”
Section: Discussionmentioning
confidence: 94%
“…Taken together, it is clear that the BNYVV isolates with T-type p25 are more aggressive to resistant plants and susceptible plants than virus isolates with O-or D-subgroup p25, although the involvement of other genes such as those related to replication, movement, or cysteinerich protein in the virulence of the T-type strain cannot be ruled out.An additional important factor affecting the BNYVV epidemics and pathogenicity is the presence of the RNA5 segment. A previous study(Tamada et al, 2021) revealed that the presence of RNA5 remarkably increased viral RNA3 accumulation levels in rootlets of the Rz1-resistant plants, suggesting that RNA5-containing virus can overcome Rz1 resistance. Similarly, the French P-type virus (with RNA5), which contains P-subgroup p25(Chiba et al, 2011), can overcome Rz1 resistance in greenhouse conditions(Bornemann & Varrelmann, 2011;Chiba et al, 2011;Pferdmenges et al, 2009).Galein et al (2018) examined the variability and virulence of BNYVV in sugar beet plant fields in the Pithiviers area, France, with different resistant genotypes over a 4-year period, where P-type p25, A-type p25 (Italy subgroup) and B-type p25 (Germany subgroup) strains were present.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Early infections result in more severe losses, while late‐season infections may not result in visible root symptoms but still cause significant reductions in sucrose content (Neher and Gallian, 2014). In addition, RNA‐5‐containing isolates may cause more severe symptoms (scab‐like symptoms on the surface of taproots) leading to more than 90% sugar yield reduction in susceptible cultivars and about 17%–59% reduction in resistant cultivars (Tamada et al., 2020). In red table beet ( B. vulgaris subsp.…”
Section: Pest Categorisationmentioning
confidence: 99%